Altered adolescents obesity metabolism is associated with hypertension: a UPLC-MS-based untargeted metabolomics study - Wu, Zhi-Ping; Wei, Wei; Cheng, Yuan; Chen, Jing-Yi; Liu, Yang; Liu, Shan; Hu, Meng-Die; Zhao, Heng; Li, Xiao-Feng; Chen, Xin (Frontiers in Endocrinology, 2023)
Objective: This study aimed to explore the relationship between plasma metabolites of adolescent obesity and hypertension; and whether metabolite alterations had a mediating effort between adolescent obesity and hypertension. Methods: We applied untargeted ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) to detect the plasma metabolomic profiles of 105 adolescents. All participants were selected randomly based on a previous cross-sectional study. An orthogonal partial least-squares- discriminant analysis (OPLS-DA) followed by univariate statistics and enrichment analysis was used to identify differential metabolites. Using logistic regression for variable selection, an obesity-related metabolite score (OMS) was constructed from the metabolites identified and hypertension risk was estimated. Results: In our study, based on P < 0.05, variable importance in projection (VIP) > 1.0, and impact-value > 0.1, we identified a total of 12 differential metabolites. Significantly altered metabolic pathways were sphingolipid metabolism, purine metabolism, pyrimidine metabolism, phospholipid metabolism, steroid hormone biosynthesis, tryptophan, tyrosine, and phenylalanine biosynthesis. The logistic regression selection resulted in a four-metabolite score (Thymidine, Sphingomyelin (SM) d40:1,4-Hydroxyestradiol, and L-Lysinamide), which was positively associated with hypertension risk (odds ratio:7.79;95% confidence interval:2.13,28.47; for the quintile 4 compared with quartile 1 of OMS) after multivariable adjustment. Conclusions: The OMS constructed from four differential metabolites was used to predict the risk of hypertension in adolescents. These findings could provide sensitive biomarkers for the early recognition of hypertension in adolescents with obesity.